The Use of Liveworksheets as an Assessment Tool to Enhance Students Conceptual Understanding and Engagement in Science Learning: A Case Study at a Junior High School - Ernawati, Ernawati; Driana*, Elin; Pramudiani, Puri (Jurnal IPA & Pembelajaran IPA, 2025)
Assessment serves as a pivotal component in education, functioning as a means to evaluate the effectiveness of the learning process. In the context of the digital era, the integration of technology into assessment practices has become increasingly essential. Digital platforms such as liveworksheets offer educators streamlined tools to design, administer, and evaluate assessments with greater efficiency and interactivity. This study explored the use of liveworksheets as an assessment tool to enhance students understanding and engagement in science learning by employing a qualitative method with a case study approach. Data were gathered through observations, interviews, and document analysis. This study involved four science teachers and twelve eighth-grade students at a junior high school in South Sumatra Province, Indonesia. The findings revealed that the teachers who participated in this study demonstrated a sound understanding of liveworksheets-based assessment instruments in science learning. These instruments were well-implemented, especially for objective questions such as multiple-choice, matching, and short-answer questions. Liveworksheets-based assessment instruments have proven effective in measuring students' understanding of science concepts. Most students derived substantial benefit from utilizing liveworksheets, as it facilitated a more interactive and engaging learning experiences. In implementing this assessment tool, the teachers faced obstacles, such as limited internet access, inadequate school devices, and students' digital learning space at home. Meanwhile, the teachers also encountered challenges such as the complexity of designing assessments, developing effective worksheets, and the limitations in question types. This study provided insights into creating more interactive and effective learning assessments, aligned with technological advancements and students' needs